Invertebrate animals of landscape gardening lawn cenoses of the city of Karaganda (area of the South-East) - Abukenova, V.S.; Bobrovskaya, Z.A. (Fundamental and Experimental Biology, 2020)
Urbanization of territories leads to the formation of ecosystems that are significantly different from natural ones. Invertebrates are the most effective and promising group of bioindicators of anthropogenic impact on natural and urban ecosystems. However, very little work has been done to study the fauna of urban ecosystems in Kazakhstan. The article presents research data on invertebrates of the Karaganda region by specialists of the Department of Zoology of Karaganda State University, carried out in different years and during periods of field practice. Analysis of invertebrate lawn communities showed the dominance of insects, in particular hymenopteran genera Formica, Myrmic, Camponotus. In second place in terms of numbers are coleoptera, among which ground beetles and staphilins prevail, as characteristic inhabitants of the city. The predominance of insects is a zonal sign. Among them there are dangerous pests: larvae of nutcracker beetles, black beetles, and lamellar beetles. Soil worms include earthworms: Lumbricus rubellus, Eisenia nordenskioldi, Appropriateode caliginosa f. typica. Predators dominate the trophic structure of lawn inhabitants, which is very characteristic of urban cenoses. The high number of predatory forms, the diversity of orders and families testifies to the favorable ecological regime of the studied lawn cenoses as a result of their long existence.